Neuropsychiatric disorders in Cushing's syndrome - Pivonello, Rosario; Simeoli, Chiara; De Martino, Maria Cristina; Cozzolino, Alessia; De Leo, Monica; Iacuaniello, Davide; Pivonello, Claudia; Negri, Mariarosaria; Pellecchia, Maria Teresa; Iasevoli, Felice; Colao, Annamaria (Frontiers in Neuroscience, 2015)
Endogenous Cushing's syndrome (CS), a rare endocrine disorder characterized by cortisol hypersecretion, is associated with psychiatric and neurocognitive disorders. Major depression, mania, anxiety, and neurocognitive impairment are the most important clinical abnormalities. Moreover, patients most often complain of impairment in quality of life, interference with family life, social, and work performance. Surprisingly, after hypercortisolism resolution, despite the improvement of the overall prevalence of psychiatric and neurocognitive disorders, the brain volume loss at least partially persists and it should be noted that some patients may still display depression, anxiety, panic disorders, and neurocognitive impairment. This brief review aimed at describing the prevalence of psychiatric and neurocognitive disorders and their characterization both during the active and remission phases of CS. The last section of this review is dedicated to quality of life, impaired during active CS and only partially resolved after resolution of hypercortisolism.